Pengembangan bahan ajar Cerita Rakyat di SD Xaverius Lubuklinggau - Inda Puspita Sari; Juwati Juwati (BAHASTRA, 2019)
The purpose of this research is to develop teaching material products sourced from folklore for fifth grade elementary school students. While the method used in this study is Research and Development (R & D). The results of development research in this study are first, students and teachers have the same needs, namely teaching materials sourced from folklore that can be used as a companion teaching materials that have been used in school. Secondly, prototypes of folklore teaching materials have cover specifications, introductory words, table of contents, learning instructions, SK/KD/indicators/goals, material, training, summary, evaluation, assessment, final training, and bibliography, biodata of the author. Third, the validation results are stated as good or feasible to be used in Xaverius Lubuklinggau Elementary School. This is based on the results of expert validation carried out on four aspects, namely the feasibility of content or material, the feasibility of language, the feasibility of the presenter and graphics. Fourth, the effectiveness test of teaching material products proves that the results of the T-Test on teaching materials are very significant. This can be seen by the schools that were sampled in the study obtained by the results of Asymp.ig. (2-teiled) greater than the significant level of 0.05.